2013
DOI: 10.1080/0020739x.2013.837522
|View full text |Cite
|
Sign up to set email alerts
|

Early error detection: an action-research experience teaching vector calculus

Abstract: This paper describes an action-research experience carried out with second year students at the School of Engineering of the National University of Entre Ríos, Argentina. Vector calculus students played an active role in their own learning process. They were required to present weekly reports, in both oral and written forms, on the topics studied, instead of merely sitting and watching as the teacher solved problems on the blackboard. The students were also asked to perform computer assignments, and their lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Mehta, Mehta, and Seals (2017) argued that aesthetic and humanistic motivations such as wonder, curiosity, and social justice are inherent reasons for doing science. Añino et al (2014) revealed that performing computer assignments has allowed students and teachers to identify errors and misconceptions that might have gone unnoticed under a more passive approach. Msoka, et al (2015) showed that students found the interactive experiments as usable as an alternative to physical experiments.…”
Section: The Student-centered Teaching Approach Problem-based Learnimentioning
confidence: 99%
“…Mehta, Mehta, and Seals (2017) argued that aesthetic and humanistic motivations such as wonder, curiosity, and social justice are inherent reasons for doing science. Añino et al (2014) revealed that performing computer assignments has allowed students and teachers to identify errors and misconceptions that might have gone unnoticed under a more passive approach. Msoka, et al (2015) showed that students found the interactive experiments as usable as an alternative to physical experiments.…”
Section: The Student-centered Teaching Approach Problem-based Learnimentioning
confidence: 99%
“…Estrategias didácticas y de aprendizaje. La lectura y la escritura en este contexto" (PID-UNER 6098 ejecución 2008-2011 13 ) (Añino et al, 2014;2015) e "Investigación acción participativa en evaluación de los aprendizajes de la matemática en Bioin-geniería" (PID-UNER 6154 ejecución 2015-2017 14 ) (Waigandt et al, 2019b).…”
Section: Introductionunclassified
“…These problems might have been because the learning process was still dominated by the lecturers (teacher-centered) instead of student-centered one (Oh, Maeng & Son, 2020), the students tended to be passive (Añino, Merino, Miyara, Perassi, Ravera, Pita & Waigandt, 2014;Çepni & Keleş, 2006), and the lecturers did not give many opportunities to students to discover knowledge through their learning experience including reading. The lecture teaching method was commonly used by most biology teachers does not offer students the opportunity to actively participate and does not promote meaningful learning of biological concepts (Oghenevwede, 2019).…”
Section: Introductionmentioning
confidence: 99%